P- and N-Depletion Trigger Similar Cellular Responses to Promote Senescence in Eukaryotic Phytoplankton - Rokitta, Sebastian D.; von Dassow, Peter; Rost, Björn; John, Uwe (Frontiers in Marine Science, 2016)
Global change will affect multiple physico-chemical parameters of the oceans, amongst them also the abundances of macronutrients like phosphorus and nitrogen that are critical for phytoplankton growth. Here we assessed the transcriptomic responses to phosphorus (P) depletion in the haploid and diploid life-cycle stage of the coccolithophore Emiliania huxleyi (RCC1217/1216) and compared the results with an existing dataset on nitrogen (N) depletion. The responses to the two depletion scenarios within one particular life-cycle stage were more similar at the transcriptome level than the responses of the two stages towards only one particular depletion scenario, emphasizing the tripartite nature of the coccolithophore genome. When cells senesced in both scenarios, they applied functionally similar programs to shut down cell cycling, re-adjust biochemical pathways and increase metabolic turnover to efficiently recycle elements. Those genes that exclusively responded to either P- or N-depletion modulated the general response to enhance scavenging, uptake and attempted storage of the limiting nutrient. The metabolic adjustments during senescence involved conserved and ancient pathways (e.g., proline oxidation or the glycolytic bypass) that prolong survival on the one hand, but on the other hand give rise to toxic messengers (e.g., reactive oxygen species or methylglyoxal). Continued senescence thus promotes various processes that lead to cell death, which can be delayed only for a limited time. As a consequence, the interplay of the involved processes determines how long cells can endure severe nutrient depletion before they lyse and provide their constituent nutrients to the more viable competitors in their environment. These responses to nutrient depletion are observable in other phytoplankton, but it appears that E. huxleyi´s outstanding endurance under nutrient deficiency is due to its versatile high-affinity uptake systems and an efficient, NAD-independent malate oxidation that is absent from most other taxa.